A Study on National University and Affiliated Colleges in Bangladesh - World Bank (Washington, DC, 2014)
A nation's utilization and creation of knowledge endeavors are globally acknowledged as the driving forces for economic development and competitiveness. Public and private investments in institutions of higher education and research require strengthening in tandem with the development of a regulatory environment that supports national and institutional growth. In recognition of these issues, the Government of Bangladesh's first Higher Education Strategic Plan (2006-2026) proposed a long-term development plan for the higher education sector, recommending that the plan will need to be cognizant of both universities and the Bangladesh National University-affiliated colleges where the majority of post-secondary graduates are enrolled. This study addresses challenges faced by a major part of the higher education sector in Bangladesh - the colleges. The objectives of the study are to: a) review and analyze the college education system of Bangladesh and b) identify policy options which will guide the government as it prepares a long-term strategy to improve the quality and relevance of higher education. This report is divided into the four key areas ripe for reform: a) access and equity, b) quality and relevance, c) financing, and d) governance.